2020
DOI: 10.1111/ppl.13053
|View full text |Cite
|
Sign up to set email alerts
|

Changes to the functional traits of phosphoenolpyruvate carboxylase following hybridization in C‐4 halophytes

Abstract: Hybridization is a relevant evolutionary mechanism linked to the invasiveness of plant species, but little is known about its effect on enzymatic activities in response to stress. We analyzed the effects of salinity on key mechanistic traits of phosphoenolpyruvate carboxylase (PEPC) enzyme for two hybrid taxa derived from native Spartina maritima (Curtis) Fernald and invasive Spartina densiflora Brongn. in comparison with their parental species. Parental species showed contrasted strategies at the PEPC level t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 79 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…Phosphoenolpyruvate carboxylase participates in plant response to various stresses and hormone signal transduction (Zhao et al, 2019;Gallego-Tévar et al, 2020). In our previous study, both SaPTPCs showed a significant upregulation under salinity while SaPEPC-1 accumulated much more transcripts than that of SaPEPC-2 (Cheng et al, 2016).…”
Section: Discussionmentioning
confidence: 91%
“…Phosphoenolpyruvate carboxylase participates in plant response to various stresses and hormone signal transduction (Zhao et al, 2019;Gallego-Tévar et al, 2020). In our previous study, both SaPTPCs showed a significant upregulation under salinity while SaPEPC-1 accumulated much more transcripts than that of SaPEPC-2 (Cheng et al, 2016).…”
Section: Discussionmentioning
confidence: 91%